2014
DOI: 10.1093/humrep/deu202
|View full text |Cite
|
Sign up to set email alerts
|

Human decidual stromal cells secrete soluble pro-apoptotic factors during decidualization in a cAMP-dependent manner

Abstract: This work was supported by the Consejería de Economía, Innovación y Ciencia, Junta de Andalucía (Grant CTS-6183, Proyectos de Investigación de Excelencia 2010 to C.R.-R.) and the Instituto de Salud Carlos III, Ministerio de Economía y Competitividad, Spain (Grants PS09/00339 and PI12/01085 to E.G.O.). E.L.-D. was supported by fellowships from the Ministerio de Educación y Ciencia, Spain and the University of Granada. The authors have no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…In this connection, we previously confirmed that the antigen phenotype of preDSCs is compatible with MSCs [5,19,25]. Functions such as cell contractility, resistance to apoptosis, and inhibition of lymphocyte apoptosis are also shared by MSCs and preDSCs [18,[26][27][28][29][30]. Further evidence of a close relationship between preDSCs and MSCs was also reported by Dimitrov et al [31].…”
Section: (Continued From Previous Page)supporting
confidence: 81%
“…In this connection, we previously confirmed that the antigen phenotype of preDSCs is compatible with MSCs [5,19,25]. Functions such as cell contractility, resistance to apoptosis, and inhibition of lymphocyte apoptosis are also shared by MSCs and preDSCs [18,[26][27][28][29][30]. Further evidence of a close relationship between preDSCs and MSCs was also reported by Dimitrov et al [31].…”
Section: (Continued From Previous Page)supporting
confidence: 81%
“…The stromal cells isolated from the decidua parietalis was confirmed to be of maternal origin31. To induce decidualization, stromal cells (2 × 10 5 cells/ml) were cultured in 24-well plates in complete DMEM in the presence of 300 nM progesterone (P4; Sigma-Aldrich) and 500 μM 8-bromo-cAMP (Sigma-Aldrich) for 7 days32. Half of the culture medium was changed on day 4, and P4 and cAMP were readded.…”
Section: Methodsmentioning
confidence: 99%
“…Resveratrol has anti‐inflammatory actions that may suppress embryo implantation directly. The decidualization of endometrial stromal cells does not entail only cellular differentiation; the alteration requires a combination of differentiation and apoptosis/senescence . In fact, decidual cells secrete proapoptotic factors during the decidualization of HESCs .…”
Section: Impact On Endometrium For Pregnancymentioning
confidence: 99%
“…The decidualization of endometrial stromal cells does not entail only cellular differentiation; the alteration requires a combination of differentiation and apoptosis/senescence . In fact, decidual cells secrete proapoptotic factors during the decidualization of HESCs . In in vitro primary cultures, the decidualization of HESCs induces senescence‐associated β‐galactosidase (SAβG) activity and increases expressions of major senescent markers, including p16 and p53 .…”
Section: Impact On Endometrium For Pregnancymentioning
confidence: 99%
See 1 more Smart Citation